Characterization and Adaptation of Anaerobic Sludge Microbial Communities Exposed to Tetrabromobisphenol A. - Emilie Lefevre (PLoS ONE, 2016)
The increasing occurrence of tetrabromobisphenol A (TBBPA) in the environment is raising questions about its potential ecological and human health impacts. TBBPA is microbially transformed under anaerobic conditions to bisphenol A (BPA). However, little is known about which taxa degrade TBBPA and the adaptation of microbial communities exposed to TBBPA. The objectives of this study were to characterize the effect of TBBPA on microbial community structure during the start-up phase of a bench-scale anaerobic sludge reactor, and identify taxa that may be associated with TBBPA degradation. TBBPA degradation was monitored using LC/MS-MS, and the microbial community was characterized using Ion Torrent sequencing and qPCR. TBBPA was nearly completely transformed to BPA via reductive debromination in 55 days. Anaerobic reactor performance was not negatively affected by the presence of TBBPA and the bulk of the microbial community did not experience significant shifts. Several taxa showed a positive response to TBBPA, suggesting they may be associated with TBBPA degradation. Some of these taxa had been previously identified as dehalogenating bacteria including Dehalococcoides, Desulfovibrio, Propionibacterium, and Methylosinus species, but most had not previously been identified as having dehalogenating capacities. This study is the first to provide in-depth information on the microbial dynamics of anaerobic microbial communities exposed to TBBPA.